Bowdoin Street Church, 35 Bowdoin Street, 1909. - Unknown (Tufts Archival Research Center, 2005)
Street-level view looking northwest of the Bowdoin Street Church on Bowdoin Street, between Cambridge Street to the north and Derne Street to the south. The facade of the church faces east toward Bowdoin Street. Houses flank the church to the north and south along Bowdoin Street. 10 7/8 x 8 1/2 overall 12 x 9 7/8 Photographs